Analisis Sikap Petani Terhadap Benih Kentang Sayur Varietas Granola Kembang, Granola Lembang, dan Dayang Sumbi di Desa Sarimukti, Kabupaten Garut - Faizah, Haura Nur; Setiawan, Iwan; Deliana, Yosini; Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Pasirwangi District is one of the areas with the highest contribution to potato production in Garut Regency which is faced with the problem of limited superior seeds which has caused a decline in potato production data. This will not only impact the level of potato production in Pasirwangi District, but will also affect the villages within it, including Sarimukti Village. Because Sarimukti Village is part of Pasirwangi District, it is likely that it will experience a similar impact. The potato varieties planted in Sarimukti Village are quite diverse, with three main varieties, namely Granola Kembang, Granola Lembang, and Dayang Sumbi. The objectives of this research are: (1) Analyzing the characteristics of vegetable potato farmers in Sarimukti Village, Pasirwangi District, Garut Regency, (2) Analyzing farmers' attitudes towards vegetable potato seeds of the Granola Kembang, Granola Lembang, and Dayang Sumbi varieties, and (3) Analyzing the attributes what needs to be paid attention to and improved in each potato seed of the Granola Kembang, Granola Lembang and Dayang Sumbi varieties. This research uses a descriptive analysis method, analysis of the Fishbein Multiattribute attitude model to determine the characteristics of farmers and farmers' attitudes towards potato seeds of the Granola Kembang, Granola Lembang and Dayang Sumbi varieties.